Gender-based Violence and ‘Feminicide’ in Queer Italian Movements: Questioning Gender, Sexuality, and the (Hetero)normative Order - Caterina Peroni (Oñati Socio-Legal Series)
This article describes the development of the Italian feminist political lexicon on gender-based violence within the security frame in the last years. After the description of the historical main issues developed by feminism during the Seventies about the relation between gender-based violence, women’s self-determination and criminal law, this paper describes the new framework of feminist and queer movements against the security policies on gender-based violence adopted by the Italian government since 2007. On the one hand, feminist movements criticized the processes of criminalization and victimization produced by the security frame and denounced the underlying nexus between sexism and racism. On the other hand, they addressed the essentialism deriving from these processes. Despite the mainstream vocabulary used the term “feminicide” in order to focus on its victimizing and alarmist aspects, contemporary feminist and queer movements thus addressed gender-based violence as a problem related to the gender stereotypes and sexist prejudices by deconstructing concepts such as gender, sexuality, and (hetero)patriarchy. In this perspective, gender-based violence is not only a form of dominion by men of women, but it also takes the shape of differential forms of inclusion and exclusion of LGBTQI persons in the neoliberal system, as in the case of homo- and trans-phobia